2016
DOI: 10.1080/19336918.2016.1155018
|View full text |Cite
|
Sign up to set email alerts
|

Developmental role of the cell adhesion molecule Contactin-6 in the cerebral cortex and hippocampus

Abstract: The gene encoding the neural cell adhesion molecule Contactin-6 (Cntn6 a.k.a. NB-3) has been implicated as an autism risk gene, suggesting that its mutation is deleterious to brain development. Due to its GPI-anchor at Cntn6 may exert cell adhesion/receptor functions in complex with other membrane proteins, or serve as a ligand. We aimed to uncover novel phenotypes related to Cntn6 functions during development in the cerebral cortex of adult Cntn6 ¡/¡ mice. We first determined Cntn6 protein and mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 48 publications
(81 reference statements)
0
24
0
Order By: Relevance
“…Current insights in the mode of action of Cntn6 were too limited to fully explain its involvement in developmental mechanisms, despite the description of phenotypes in null mutant mice, such as biochemical interactors (Zuko et al, 2013). These phenotypes included a developmental delay of the corticospinal tract, a misorientation of apical dendrites in the cortex, altered numbers of subtype specific projection neurons and interneurons in the cortex, and an increase in neuronal cell death during cerebellar development (Ye et al, 2008; Sakurai et al, 2009; Pinto et al, 2010; Huang et al, 2011b; Zuko et al, 2016). Also, significant reduction in glutamatergic synapses was found in the hippocampus and in the cerebellum of Cntn6 null-mutants (Sakurai et al, 2009, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Current insights in the mode of action of Cntn6 were too limited to fully explain its involvement in developmental mechanisms, despite the description of phenotypes in null mutant mice, such as biochemical interactors (Zuko et al, 2013). These phenotypes included a developmental delay of the corticospinal tract, a misorientation of apical dendrites in the cortex, altered numbers of subtype specific projection neurons and interneurons in the cortex, and an increase in neuronal cell death during cerebellar development (Ye et al, 2008; Sakurai et al, 2009; Pinto et al, 2010; Huang et al, 2011b; Zuko et al, 2016). Also, significant reduction in glutamatergic synapses was found in the hippocampus and in the cerebellum of Cntn6 null-mutants (Sakurai et al, 2009, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampal structure plays an important role in spatial learning and memory. It has been reported that the length and area size of the suprapyramidal bundle (SPB) in the hippocampus were significantly increased in Cntn6 −/− mice (Zuko et al., ). Here, we examined whether Cntn6 deficiency affected hippocampus‐related behavior in the Morris water maze task.…”
Section: Resultsmentioning
confidence: 99%
“…Amila Zuko et al. found that Cntn6 deficiency in the dentate gyrus (DG) may impair the fasciculation of mossy fibers that innervate pyramidal cells in the hippocampus (Cremer, Chazal, Goridis, & Represa, ; Heyden, Angenstein, Sallaz, Seidenbecher, & Montag, ; Montag‐Sallaz, Schachner, & Montag, ; Zuko et al., ). Some studies showed that F3/Contactin, another member of the contactin family, promotes hippocampal neurogenesis in adult mice (Mercati et al., ; Puzzo et al., ; Sakurai et al., , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANAPC13 functions in the ubiquitin-mediated proteolysis pathway. CNTN6 encodes a neural adhesion molecule which has been associated with intellectual disability [Kashevarova and others 2014] in children, and copy number variants in this gene have recently been identified it as a candidate for a wide spectrum of neurobehavioral disorders [Hu and others 2015]; this gene may also function in a large number of protein interaction networks important for normal brain development [Zuko and others 2016]. The gene CSMD1 has been associated with sporadic Alzheimer’s disease [Parcerisas and others 2014], schizophrenia [Koiliari and others 2014], cannabis dependence [Koiliari and others 2014], and other neuropsychiatric disorders.…”
Section: Discussionmentioning
confidence: 99%